A STUDY ABOUT FAILURE SEMESTER SYSTEM FOR GENERAL COURSES IN MP - Dr. Paras Jain (International Journal of Research Science and Management, 2017)
A semester system is more challenging for students while it is difficult for teachers and college management to conduct exams every six months. It proved as a burden on students, colleges and universities. Semester system is perceived to be better than annual system in institutions of higher learning since the students could be kept busy all through the year. The semester system is not at fault, but it just does not suit the model of Indian Universities. Present study is focused on students, teacher’s, administrator’s view.